Kajian Ekologi Sastra (Ekokritik) dalam Antologi Puisi Negeri di atas Kertas Karya Komunitas Sastra Nusantara: Perspektif Lawrence Buell - Anisatul Jannah; Agik Nur Efendi (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Research on literary ecology (ecocriticism) has been widely conducted, but studies on the anthology of poems Negeri di Atas Kertas using Lawrence Buell's perspective are still rare. This study aims to describe (1) the relationship between nature and humans and (2) the form of ecocriticism in the poems using Buell's theory. The method used is descriptive qualitative with the primary data source being the anthology of poems Negeri di Atas Kertas by the Komunitas Sastra Nusantara, collected through a note-taking technique. Buell's theory identifies three aspects of ecocriticism, namely (1) non-human elements that play a role in the historical relationship between humans and nature, (2) the position of humans as non-dominant over nature, and (3) the dynamic nature of the environment in line with the passage of time. The results of the study show that three poems reflect the relationship between humans and nature, namely Tukang Sapu Jalan (Street Sweeper), Bunda Kami Kartini (Our Mother Kartini), and Ayah (Father). Meanwhile, four other poems contain ecocritical elements, namely Pagi Probolinggo (Morning in Probolinggo), Anak Pulau (Island Child), Bumi Pertiwi Bersabda (Mother Earth Speaks), and Negeriku Kembali Berduka (My Country Mourns Again). The relationship between humans and nature in these poems reflects Buell's principles, highlighting the emotional intimacy between humans and the natural environment.